Efficacy of Zest, Resolve, and Harmony Tank Mixes Used Sequentially in Irrigated Acetolactase Synthase (ALS)-Resistant Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Palmer amaranth control was best when Cinch was applied preemergence (PRE) followed by Zest plus atrazine postemergence (POST) or when Cinch ATZ was applied early postemergence (EPOST) with Zest and atrazine. Most herbicides provided excellent crabgrass control. Shattercane control was excellent with all herbicides except Cinch ATZ applied PRE. Minor sorghum stunting was observed with some treatments three days after application, but sorghum had completely recovered within one week. Herbicide-treated grain sorghum yielded 48 to 93 bu/a more grain than untreated sorghum. Sorghum yields were best when Cinch or Cinch ATZ was applied PRE followed by Zest and atrazine POST, or when Cinch ATZ was applied with Zest and atrazine EPOST.
Keywords: Herbicide-resistant sorghum